2019
DOI: 10.1016/j.scitotenv.2019.02.273
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid receptor antagonism as a contributory mechanism for adipogenesis induced by environmental mixtures in 3T3-L1 cells

Abstract: We previously demonstrated that indoor house dust extracts could induce adipogenesis in preadipocytes, suggesting a potential role for indoor contaminant mixtures in metabolic health. Herein, we investigated the potential role of thyroid receptor beta (TRβ) antagonism in adipogenic effects (dust-induced triglyceride accumulation and pre-adipocyte proliferation) following exposure to environmental mixtures (indoor house dust extracts). Concentrations of specific flame retardants were measured in extracts, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 78 publications
(112 reference statements)
0
10
0
1
Order By: Relevance
“…This could be one possible explanation for why the concentrations of OPEs designated as inactive in Tox21 screening assays had statistically significant associations with PPARc antagonism in dust samples. That result could also be partly explained by the fact that the inactive-designated OPEs are sometimes correlated with other unmeasured FRs or phthalate plasticizers (Bi et al 2018;Castorina et al 2017;Kassotis et al 2019;Kollitz et al 2018) or could be influenced by the small error that could be introduced from using designations based on a PPARc antagonism assay with a different reporter gene (beta-lactamase) and human cell line tissue type (embryonic kidney) than our dust assays. However, another previous study that measured PPARc antagonism of OPEs using the same luciferase reporter gene assays and human osteosarcoma cell lines as our study was consistent in classifying the four Tox21-inactive chemicals found in our samples at the highest concentrations as inactive (Suzuki et al 2013).…”
Section: Methods Evaluation Of Potency-weighted Concentrations Of Chemical Classesmentioning
confidence: 98%
See 1 more Smart Citation
“…This could be one possible explanation for why the concentrations of OPEs designated as inactive in Tox21 screening assays had statistically significant associations with PPARc antagonism in dust samples. That result could also be partly explained by the fact that the inactive-designated OPEs are sometimes correlated with other unmeasured FRs or phthalate plasticizers (Bi et al 2018;Castorina et al 2017;Kassotis et al 2019;Kollitz et al 2018) or could be influenced by the small error that could be introduced from using designations based on a PPARc antagonism assay with a different reporter gene (beta-lactamase) and human cell line tissue type (embryonic kidney) than our dust assays. However, another previous study that measured PPARc antagonism of OPEs using the same luciferase reporter gene assays and human osteosarcoma cell lines as our study was consistent in classifying the four Tox21-inactive chemicals found in our samples at the highest concentrations as inactive (Suzuki et al 2013).…”
Section: Methods Evaluation Of Potency-weighted Concentrations Of Chemical Classesmentioning
confidence: 98%
“…Few studies have measured the activities of dust toward nuclear hormone receptors using cell-based assays (Chou et al 2015;Fang et al 2015;Hamers et al 2020;Kassotis et al 2019;Suzuki et al 2007;Vandermarken et al 2016). For example, Suzuki et al (2013) reported that certain measured PBDEs or OPEs in household dust were probable contributors to ERa activation and AR suppression.…”
Section: Introductionmentioning
confidence: 99%
“…A recent follow-up to this study evaluated the adipogenic activity of 137 house dust extracts from central NC households and attempted to determine putative causative chemicals, molecular mechanisms, and potential impacts on human metabolic health (264). We reported that 90% of the dust extracts exhibited significant adipogenic activity, < 60% via significant triglyceride accumulation, and >70% of samples via significant pre-adipocyte proliferation, with >40% of effects occurring at < 10 μg dust/well (264). Increasing dust-induced triglyceride accumulation was positively correlated with serum thyroid stimulating hormone levels in adult residents, and negatively correlated with serum free triiodothyronine (T3) and thyroxine (T4) (264).…”
Section: Metabolic Disruption Potential Of Environmental Mixturesmentioning
confidence: 99%
“…We reported that 90% of the dust extracts exhibited significant adipogenic activity, < 60% via significant triglyceride accumulation, and >70% of samples via significant pre-adipocyte proliferation, with >40% of effects occurring at < 10 μg dust/well (264). Increasing dust-induced triglyceride accumulation was positively correlated with serum thyroid stimulating hormone levels in adult residents, and negatively correlated with serum free triiodothyronine (T3) and thyroxine (T4) (264). Interestingly, proliferation tended to be positively correlated with residents' body mass index (BMI; p < 0.10), potentially suggesting adipogenic chemicals present in the dust are associated with the weights of residents, but further research with larger sample sizes are needed to substantiate this.…”
Section: Metabolic Disruption Potential Of Environmental Mixturesmentioning
confidence: 99%
See 1 more Smart Citation